Combinatorial fluorapatite-based scaffolds substituted with strontium, magnesium and silicon ions for mending bone defects - Golafshan, Nasim; Alehosseini, Morteza; Ahmadi, Tahmineh; Talebi, Ardeshir; Fathi, Mohammadhossein; Kharaziha, Mahshid; Orive, Gorka; Castilho, Miguel; Dolatshahi-Pirouz, Alireza (Elsevier Limited, 2021)
In bone tissue engineering, ionic doping using bone-related minerals such as magnesium (Mg) or strontium (Sr) is a promising strategy to make up for the inherent disadvantages (low solubility) of various apatite-based materials (such as fluorapatite (FAp) and hydroxyapatite (HA)). Therefore, some studies in recent years have tried to address the lack-of-methodology to improve the properties of bioceramics in the field. Even though the outcome of the studies has shown some promises, the influence of doped elements on the structures and properties of in-vitro and in-vivo mineralized FAp has not been investigated in detail so far. Thus, it is still an open question mark in the field. In this work, strontium modified fluorapatite (Sr-FAp), magnesium and silicon modified fluorapatite (Mg-SiFAp) bioceramics were synthesized using a mechanical alloying methodology. Results showed that the doped elements could decrease the crystallinity of FAp (56%) to less than 45% and 39% for Sr-FAp and Mg-SiFAp, respectively. Moreover, in-vitro studies revealed that Sr-FAp significantly enhanced osteogenic differentiation of hMSCs, after 21 days of culture, compared to Mg-SiFAp at both osteogenic and normal media. Then, in vivo bone formation in a defect of rat femur filled with a Sr-FAp and Mg-SiFAp compared to empty defect was investigated. Histological analysis revealed an increase in bone formation three weeks after implanting Sr-FAp compared to Mg-SiFAp and the empty defect. These results suggest that compared to magnesium and silicon, strontium ion significantly promotes bone formation in fluorapatite, making it appropriate for filling bone defects.
Keywords: Bone tissue engineering; Flourapatite; Magnesium; Osteoinductive; Strontium; Taverne; General Materials Science; Condensed Matter Physics; Mechanics of Materials; Mechanical Engineering